21.5k views
5 votes
Find the inverse of the function.

Find the inverse of the function.-example-1

2 Answers

0 votes

Answer:

Option A

Explanation:

f(n) =∛n-2

y= ∛n-2

Interchange y and n

n =∛y-2

Subtract -2 on both sides

n+2 = ∛y

both both sides to the 3rd power:

(n+2) to the 3rd power = y

Inverse :

f-1(n) = (n+2) to the 3rd power (option A)

User Bruno Coelho
by
5.5k points
4 votes

Answer:

A)
f^(-1)(n)= (n+2)^3

Explanation:


f(n) = \sqrt[3]{n} -2


y = \sqrt[3]{n} -2


y = n^(1/3)-2


n = y^(1/3) -2


n + 2 = y^(1/3)


y = (n + 2) ^3


f^(-1)(n) = (n + 2)^3

Hope this helps!

User Nguyen Lam Phuc
by
5.4k points